(3TQM Ydi EjSGZhLi GdCHOis - (3CHh GdYHGS CMeO Hf YHO GdQMef GdGHOj GdHLGFjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOG UhQ GdMbGFb hHYO aEfg deG cGf cJGH GdTjN GdEeGe CKjQ GdOjf GdCHgQfi GdehShe HEjSGZhLi eJVefkG dbhGYO s
(3BNQgG (B:s
(3bhdg GdYeOI gi GdHQgGf hfaYfG HHQcJg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs